Structural transitions under high-pressure in a langasite-type multiferroic Ba3TaFe3Si2O14 - Naumov, P. G.; Ksenofontov, V.; Lyubutin, I. S.; Medvedev, S. A.; Barkalov, O. I.; Palasyuk, Taras; Magos-Palasyuk, E.; Felser, Claudia (Solid State Sciences, 2015)
The iron containing langasite family compound Ba3Ta57Fe3Si2O14 was studied at high pressure up to 30 GPa at room temperature by means of in situ X-ray diffraction, Raman and Mössbauer spectroscopies in diamond anvil cell. Two structural transitions at pressures ∼5 and ∼20 GPa are observed. At ∼5 GPa, the low-pressure trigonal P321 phase undergoes phase transition to the most likely P3 structure as manifested by slight increase in the c/a ratio and by anomalies of the Mössbauer and Raman spectra parameters. At ∼20 GPa, the first order phase transition to monoclinic structure occurred with a drop of unit cell volume by 9%. The appearance of the ferroelectric state at such transitions is discussed in connection with the multiferroic properties.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Diamond anvil cell; High pressure; Multiferroic properties; Mössbauer spectroscopy; Raman spectroscopy; X-ray diffraction